Dampak Pemberlakuan Sistem Zonasi terhadap Daya Saing Pelajar di Indonesia - Tasyirifiah, Tahniah; Pitaloka, Anna Fadhila (Lembaga Yasin AlSys, 2023)
Zoning is a new system promoted by the government as a program that is expected to equalize education in Indonesia. However, in practice the zoning itself is felt to be immature and seems rushed because there are still high disparities between schools in Indonesia which can be seen from the differences in quality, facilities, facilities & infrastructure so that this system is considered unfair. Zoning replaces the National Examination (UN) scores which used to serve as a reference for whether or not students are accepted to continue their education at public schools so that students whose homes are close to public schools don't have to work hard and study competitively because the zoning system allows them to to be accepted into public schools. This is seen as reducing the motivation and competitiveness of students in Indonesia because previously one of their motivations in studying was to achieve their dreams of being able to continue their education at their favorite state schools. The data collection in this article uses the Systematic Literature Review method where data is obtained from various books, articles, and journals accessed by the author online.